PENGARUH KEADILAN ORGANISASIONAL TERHADAP KOMITMEN ORGANISASI DENGAN JARAK KEKUASAAN SEBAGAI VARIABEL MODERATING (Studi pada PT. PLN (Persero) APJ Semarang) - Nurcahyani, Dewi; Masâ€™ud, Fuad (Diponegoro Journal of Management, 2016)
This research aims to examine the impact organizational justice to organizational commitment and examine the role of power distance as moderating variable to the relationship between organizational justice to the organizational justice. This research is conducted to the employers of PT. PLN (Persero) APJ Semarang. Using survey method through Moderated Regression Analysis (MRA). The number of sample used are 77 employees which has represented of six division in PT. PLN (Persero) APJ Semarang.The result shows that organizational justice has positive significant impact Â to organizational commitment. Beside, the result of MRA test shows that power distance moderate the relationship between organizational justice and organizational commitment.